What are appropriate initial tests when evaluating a patient for possible pheochromocytoma?. Issue 1 (January 2017) - Croft, Devin; Clark, Michael
Abstract : EVIDENCE‐BASED ANSWER : The most accurate initial test for suspected pheochromocytoma is plasma‐free metanephrines, with a sensitivity of 94% to 99% and a specificity of 89% to 96% (positive likelihood ratio [LR+] 9–23, negative likelihood ratio [LR‐] 0.01–0.067). An acceptable alternative, especially when attempting to rule out the disease, is urine‐fractionated metanephrines, with a sensitivity of 97% and a specificity 69% (LR+ 3.1, LR‐0.04) (SOR: A, diagnostic cohort studies and practice guideline).